Strains of Mycobacterium tuberculosis transmitting infection in Brazilian households and those associated with community transmission of tuberculosis. (May 2017) - Vinhas, Solange Alves; Jones-López, Edward C.; Ribeiro Rodrigues, Rodrigo; Gaeddert, Mary; Peres, Renata Lyrio; Marques-Rodrigues, Patricia; de Aguiar, Paola Poloni Lobo; White, Laura Forsberg; Alland, David; Salgame, Padmini; Hom, David; Ellner, Jerrold J.; et al.
Abstract: Molecular epidemiologic studies have shown that the dynamics of tuberculosis transmission varies geographically. We sought to determine which strains of Mycobacterium tuberculosis (MTB) were infecting household contacts (HHC), and which were causing clusters of tuberculosis (TB) disease in Vitoria-ES, Brazil. A total of 741 households contacts (445 TST +) and 139 index cases were characterized according to the proportion of contacts in each household that had a tuberculin skin test positive: low (LT) (≤40% TST+), high (HT) (≥70% TST+) and (40–70% TST+) intermediate (IT) transmission. IS 6110 -RFLP and spoligotyping analysis were performed only 139 MTB isolates from index cases and 841 community isolates. Clustering occurred in 45% of the entire study population. There was no statistically significant association between MTB household transmission category and clustering. Within the household study population, the proportion of clusters in HT and LT groups was similar (31% and 36%, respectively; p = 0.82). Among index cases isolates associated with households demonstrating TST conversion, the frequency of unique pattern genotypes was higher for index cases of the LT compared to HT households (p = 0.03). We concluded that clusters and lineages associated with MTB infection in HT households had no proclivity for increased transmission of TB in the community.